PERLINDUNGAN HAK-HAK KEPERDATAAN ANAK TERLANTAR MELALUI PENGANGKATAN ANAK - Vivi Ariesthia Hani (2021)
Every child who is born must get civil rights from his parents. These civil rights cannot be accepted by abandoned children. Abandoned children are the responsibility of society and the state to be able to provide their civil rights. One way to provide the civil rights of neglected children is the adoption process. Adopted child is a child whose rights are transferred from the sphere of authority of the family of the parent, legal guardian, or other person responsible for the care, education and raising of the child into the family environment of the adoptive parent. Adoption or adoption is an alternative path taken for a family that has not been blessed with children or wants to add members to the family. This study aims to analyze and find out what civil rights are according to civil law and to know the process of adopting abandoned children that can protect their civil rights. This study uses a normative juridical method with a statutory approach. Primary and secondary legal materials are obtained through librarian research, which is analyzed descriptively and analytically. The purpose of this research is to explain the form of protection for the rights of neglected children and the legal process of adoption so that the civil rights of neglected children can be granted. The results showed that the state should provide a solution to the fulfillment of the civil rights of neglected children through the process of legal adoption. The conclusion of this research is that protection of the civil rights of neglected children can be obtained through the process of adoption. The process of adopting a child legally provides legal certainty for neglected children to get their civil rights.